2017
DOI: 10.1111/ijfs.13592
|View full text |Cite
|
Sign up to set email alerts
|

Gelation properties of goose liver protein recovered by isoelectric solubilisation/precipitation process

Abstract: Summary Isoelectric solubilisation/precipitation (ISP) process was applied to goose liver (GL) for protein extraction. The gelation properties of proteins extracted by acid processes (ACP, pH 2.0, 2.5 and 3.0) and alkaline processes (ALP, pH 11.0, 11.5 and 12.0) were estimated, where the unextracted ground GL was set as the control. Nearly 58.39~79.00% of GL proteins were recovered by ISP treatments. High molecular weight (100~250 kDa) proteins were found to be partially hydrolysed by ACP, while few changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…In this sense, analyzing raw turkey and buffalo liver and using distilled water as the extracting medium, Zouari et al [70] and Devatkal et al [71] found percentages of protein solubility of 55 and 20–40% respectively, which was closer to the figures obtained in the present study. Similar results were reported in protein concentrates from goose liver at pH 6–7 [4] . Moreover, the difference between the soluble protein contents in the present analysis and the studies by Nuckles et al [69] and Steen et al [5] for pork liver might also be attributed to the aforementioned aspects, such as nutritional factors, the physiological state, sex, genetic background or age.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In this sense, analyzing raw turkey and buffalo liver and using distilled water as the extracting medium, Zouari et al [70] and Devatkal et al [71] found percentages of protein solubility of 55 and 20–40% respectively, which was closer to the figures obtained in the present study. Similar results were reported in protein concentrates from goose liver at pH 6–7 [4] . Moreover, the difference between the soluble protein contents in the present analysis and the studies by Nuckles et al [69] and Steen et al [5] for pork liver might also be attributed to the aforementioned aspects, such as nutritional factors, the physiological state, sex, genetic background or age.…”
Section: Resultssupporting
confidence: 90%
“…Of the different revalorization strategies that are being investigated, those that could be highlighted are aiming to extract its high protein fraction (81.9 %, d.b.) [3] since the liver is considered as a protein source of high biological value and digestibility [4] . In this sense, the functional protein fraction of pork liver has exhibited adequate emulsifying, gelling and foaming properties compared to other commercial proteins widely used in the meat industry [5] .…”
Section: Introductionmentioning
confidence: 99%
“… Choi et al (2013) observed the water content in the porcine liver changed from 77% at 25°C to 55% at 80°C. Li et al (2018) reported a cooking loss of 25% in fresh goose liver after heating to 80°C and holding for 30 min, which is similar to the result of fresh chicken liver in the current study. Xiong et al (2020) reported a cooking loss of 13% in fresh chicken livers after heating at 80°C for 30 min without indicating the actual temperature the liver reached.…”
Section: Resultssupporting
confidence: 89%
“…Increasing the heating temperature to higher than 60°C caused thermal aggregation of the protein, resulting in increased shear resistance. The liver proteins underwent aggregation and complex formation due to cross-links after heating to 70°C, and the network became stronger as temperature increased to 90°C ( Li et al, 2018 ). The more considerable area shrinkage and cooking loss at higher temperatures also contributed to a denser and firmer structure ( Roldán et al, 2013 ; Choi et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation